Polyphenazine films as inhibitors of copper corrosion - Romeiro, Andreia (2013)
The polyphenazines poly(brilliant cresyl blue) (PBCB), poly(Nile blue A) (PNB) and poly(safranine T) (PST) have been investigated as corrosion protection films on copper electrodes by open circuit measurements, Tafel plots and electrochemical impedance spectroscopy, complemented by scanning electron microscopy. Pure copper electrodes were initially passivated in sodium oxalate or hydrogen carbonate solutions, to inhibit copper dissolution at potentials where phenazine monomer oxidation occurs, before electropolymerisation by potential cycling. The corrosion inhibition of these films was tested in 0.10 M KCl solution. It was found that, after long immersion times, the best protection efficiency was with PNB films formed on copper passivated in sodium hydrogen carbonate solution.